2023
DOI: 10.1002/lary.30816
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Late‐Stage Meniere's Disease and Vestibular Functional Impairment on Hippocampal Atrophy

Abstract: ObjectiveWe investigated correlations among clinical features, degree of inner ear endolymphatic hydrops (EH), and hippocampal volume (HV) in different stages of Meniere's disease (MD).MethodsFrom February 2021 to April 2022, clinical data were collected from 99 patients (39 males, 60 females, mean age: 50.4 ± 10.0 [range: 26–69] years) with unilateral MD admitted to the Department of Vertigo Disease of Shandong ENT Hospital. The left and right ears were affected in 64 and 35 patients, respectively. There were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…A study revealed that individuals with MD and right-sided hearing loss exhibited more prominent memory and concentration difficulties than those with left-sided hearing loss ( 157 ). Previous research has indicated that individuals with MD display signs of hippocampal atrophy, which could potentially contribute to their cognitive decline ( 158 , 159 ). A recent study found that patients with MD were more likely to have cognitive deficits than benign paroxysmal positional vertigo ( 160 ).…”
Section: Cognitive Impairment In Different Vestibular Disordersmentioning
confidence: 99%
“…A study revealed that individuals with MD and right-sided hearing loss exhibited more prominent memory and concentration difficulties than those with left-sided hearing loss ( 157 ). Previous research has indicated that individuals with MD display signs of hippocampal atrophy, which could potentially contribute to their cognitive decline ( 158 , 159 ). A recent study found that patients with MD were more likely to have cognitive deficits than benign paroxysmal positional vertigo ( 160 ).…”
Section: Cognitive Impairment In Different Vestibular Disordersmentioning
confidence: 99%
“…Additionally, the subjective nature of the assessment necessitates trained examiners to interpret subtle changes. Newer versions like the quantified Romberg test, employing force plates or video-based analysis, can provide more objective data [21].…”
Section: Limitations and Refinementsmentioning
confidence: 99%
“… Van Cruijsen et al (2007) found that MD was associated with an atrophy of the left HPC, as did Seo et al (2016) . On the other hand, Jian et al (2023) reported that unilateral, late stage MD was associated with a bilateral HPC atrophy.…”
Section: Evidence For Hippocampal Volume Changes Following Vestibular...mentioning
confidence: 99%